Trend, Associated Factors and Concordance of Obesity by Body Mass Index, Waist Circumference and Waist-Height Ratio in Adolescents. An Analysis of a 4-Year National Survey - Mamani, Lisseth; Vásquez Romero, Luisa Erika Milagros; Torres-Malca, Jenny Raquel; Loayza-Castro, Joan A.; Romero-Figueroa, María del Socorro; Vera-Ponce, Víctor Juan; Cruz-Vargas, Jhony A. De La (International Journal of Statistics in Medical Research, 2023)
Introduction: Regarding diagnosis, identifying reliable anthropometric measures to detect adolescent obesity is fundamental. However, in this age group has different definitions, either according to the body mass index (BMI), the waist circunference (WC) and the waist-height ratio (WHtR), making the measurement of this inaccurate. Objective: This study analyzed the prevalence, trends, and factors associated with obesity in Peruvian adolescents using data from the Demographic and Health Survey (ENDES) for 2019-2022. Methods: A secondary data analysis was conducted on 14,330 adolescents aged 15 to 19. The response variable was obesity, defined in three different ways. General obesity was assessed using the BMI was ≥ 2 standard deviations. 2) Abdominal obesity was defined through WC, with cutoff points ≥ 80.5 cm in men and ≥ 81 cm in women. 3) The relevant indicator for obesity was the WHtR, with a cutoff point ≥ 0.5. The associated factors to be evaluated were sex, age, natural region, marital status, education level, wealth, area of residence, alcohol consumption, and physical disability. Results: The study found that based on BMI, WC, and WHtR respectively, approximately 12.80%, 29.72%, and 24.27% of participants were considered obese. Significant associations were found between obesity and variables such as gender, natural region, marital status, wealth index, area of residence, education level, alcohol consumption, and physical disability. Conclusion: This research uncovered an alarmingly prevalence occurrence of obesity among adolescents in Peru with fluctuating patterns over time, emphasizing the need to tackle the interconnected issues contributing to this health concern. These findings can help inform and guide obesity prevention and control strategies in this population.